Implementation and Preliminary Results of an Emergency Department Nontargeted, Opt‐out Hepatitis C Virus Screening Program. (20th July 2018) - Schechter‐Perkins, Elissa M.; Miller, Nancy S.; Hall, Jon; Hartman, Joshua J.; Dorfman, David H.; Andry, Chris; Linas, Benjamin P.
Abstract: Background: Emergency department (ED) visits provide an opportunity for hepatitis C virus (HCV) screening for patients who otherwise might not be tested. We report on a novel nontargeted, opt‐out HCV screening and linkage‐to‐care (LTC) program implemented in an urban ED. Methods: This is a descriptive analysis from 3 months (November 2016–January 2017) of a nontargeted, opt‐out ED HCV screening and LTC program among patients at least 13 years old undergoing phlebotomy for clinical purposes. A multipurpose best practice advisory (BPA) alerted providers to the program and generated order labels. For patients who authorized testing, specimens were drawn in the ED for HCV antibody (Ab) and reflex confirmatory RNA tests. Public health navigators attempted to contact RNA‐positive patients and arrange outpatient visits. Results: HCV Ab tests were performed on 3, 808 patients, a 6, 950% increase from preprogram. The proportion of HCV Ab test positivity was 13.2% (504/3, 808, 95% confidence interval [CI] = 12.2%–14.3%) and of those 97.8% (493/504) had a follow‐up RNA test performed. A total of 292 were confirmed positive for active infection, for an overall RNA positivity rate of 7.7% (95% CI = 6.8%–8.5%). Of those with active infection, 155 (53%) were outside the Centers for Disease Control and Prevention birth cohort for increased risk for HCV including 46 (15.8%, 95% CI = 11.8%–20.4%) who also did not report injection drug use. Linkage attempts were documented on 223 (76.4%) patients and appointments were scheduled for 102 (38% of attempted). Sixty‐six patients attended their LTC visit (22.5% of all RNA‐positive patients, 30% of linkage‐eligible patients). Conclusions: Nontargeted opt‐out HCV testing can be successfully implemented in an ED setting. A number of patients diagnosed were outside traditional risk groups. Once diagnosed, an ED population may be difficult to engage in care, but a structured interdisciplinary program can successfully link patients to HCV care.